2016
DOI: 10.1016/j.cjche.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Inocula selection in microbial fuel cells based on anodic biofilm abundance of Geobacter sulfurreducens

Abstract: Microbial fuel cells (MFCs) rely on microbial conversion of organic substrates to electricity. The optimal performance depends on the establishment of a microbial community rich in electrogenic bacteria. Usually this microbial community is established from inoculation of the MFC anode chamber with naturally occurring mixed inocula. In this study, the electrochemical performance of MFCs and microbial community evolution were evaluated for three inocula including domestic wastewater (DW), lake sediment (LS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The EIS data for the anode and cathode thus explained that the FeC-MFC gave the highest maximum current density, followed by the AiC-MFC and the DOC-MFC. It has been found that substrate loading rate and external resistance determines the maximum charge and current, which can be generated in a MFC [5,12]. Increasing substrate loading rate at decreasing external resistance was investigated to optimize electricity generation in the MFCs as shown in Figure 5.…”
Section: Current Generation In Relation To Substrate Loading Rate Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The EIS data for the anode and cathode thus explained that the FeC-MFC gave the highest maximum current density, followed by the AiC-MFC and the DOC-MFC. It has been found that substrate loading rate and external resistance determines the maximum charge and current, which can be generated in a MFC [5,12]. Increasing substrate loading rate at decreasing external resistance was investigated to optimize electricity generation in the MFCs as shown in Figure 5.…”
Section: Current Generation In Relation To Substrate Loading Rate Andmentioning
confidence: 99%
“…Bioethanol effluent is suitable as substrate for current generation in MFCs when the MFC is initiated using acetate [6]. However, further performance improvement can be achieved by the use of inocula from different environmental sources such as lake sediment [5]. In addition, an efficient cathode process is required before the use of MFC for current generation is feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection and development of AC was targeted at introducing a cost-effective electrode material for use in MFCs. The successful inoculation of AC indicated that an improvement in power generation can be achieved through post-inoculation cycles [24,25]. Numerous cycles of operation are known to improve biofilm and increase the total power generated.…”
Section: Electricity Generation From Palm Kernel Shell Acmentioning
confidence: 99%
“…Bacterial species found in AC biofilms also included G. sulfurreducens, E. cancerogenus and D. acetexigens. In the MFC study by Sun et al, all the identified bacteria except D. acetexigens were identified, which indicates a large similarity in the microbial community due to the use of wastewater, even though the inocula have been obtained from Denmark, Europe in that study [24]. EIS was thereby a fast and useful technique for evaluation of the electrode materials and the inocula.…”
Section: Microbial Analysis Of Cp and Ac Biofilmsmentioning
confidence: 99%